Adaptation of the political economy of the grassroots Tionghoa ethnic in Bangka Island, Indonesia - Ibrahim Ibrahim; Arief Hidayat; Herza Herza (Masyarakat, Kebudayaan dan Politik, 2022)
Since the 17th century, various Tionghoa ethnic groups migrated from mainland China to Southeast Asia, including Indonesia. These ethnic groups migrated in accordance with the power in government. In Bangka Island, the Tionghoa had become part of the tin exploitation process hundreds of years before colonization. When new policies and changes are made on tin mining by the government, it negatively affects the socioeconomic life of this ethnic group, which was initially known as tin laborers. This study aims to determine the adaptation of the Tionghoa political economy in Bangka Island. The research method used is qualitative with literature review, interview, and observation as the data collecting technique conducted from January to December 2021. The result showed that the government largely determined the rule of tin by the Tionghoa ethnics. They became partners, administrators, illegal and main players during the Palembang Sultanate, colonial period, Old and New Orders, and the post-1998 reform period. This study discovered that Tionghoa at the elite and grassroots levels are actually different. In general, this study concludes that the Chinese at the grassroots tend to be distant from the advantages of tin due to limited capital and access.